Collective cell migration: A mechanistic perspective - Vedula, Sri Ram Krishna; Ravasio, Andrea; Lim, Chwee Teck; Ladou, Benoit (Physiology, 2013)
Collective cell migration is fundamental to gaining insights into various mportant biological processes such as wound healing and cancer metastasis. In particular, recent in vitro studies and in silico simulations suggest that mechanics can explain the social behavior of multicellular clusters to a large extent with minimal knowledge of various cellular signaling pathways. These results suggest that a mechanistic perspective is necessary for a comprehensive and holistic understanding of collective cell migration, and this review aims to provide a broad overview of such a perspective. © 2013 Int. Union Physiol. Sci./Am. Physiol. Soc.
CRIS-Team Scopus Importer:2024-02-19